THU0506 Cross-sectional analysis of the associations between fibromyalgia and cancer. (12th June 2018) - Lichtenstein, A.; Tiosano, S.; Comaneshter, D.; Cohen, A.D.; Amital, H.
Abstract : Background: Fibromyalgia syndrome (FMS) is defined as chronic widespread musculoskeletal pain and tenderness with concomitant mood and cognitive dysfunction. Several comorbidities have been reported to be associated with FMS. However, these studies are mostly based on small populations and lack solid evidence. Objectives: To evaluate the association of FMS with Cancer diagnoses. Methods: This cross-sectional study used the database of the largest Health Maintenance Organisation in Israel, Clalit Health Services, serving more than 4 million members. FMS patients were compared to age- and sex-matched controls regarding comorbid Cancer diagnoses. Chi-square and t-tests were used for univariate analysis, . Results: Our study utilised data from 14, 296 FMS patients and 71 324 age- and sex-matched controls. FMS patients compared to controls had a higher proportion of the following types of cancer: Cervix and Uteri, Connective Tissue Sarcoma, Thyroid, Non Hodgkin Lymphoma (NHL) and Benign brain tumours (OR=1.39, 1.60, 1.68, 1.26, 1.87 respectively, P value<0.005) – See table 1. Conclusions: Study results show a higher proportion of malignancy diagnoses amongst FMS patients compared to matched controls. Accordingly, in treating FMS patients, physicians should bear in mind the likelihood of concomitant tumour as it might explain various FMS symptoms, and more importantly, shorten a patients' time for diagnosis and treatment of the oncological condition. Disclosure of Interest: None declared